An Enhancement of Outer-Independent Total Roman Domination in FIS Graphs Using Adaptive Neuro Chromatic Polynomial Fuzzy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, we begin by examining Outer-Independent Total Roman (OITRD) and introduce limits on the number of total external free Roman workers associated with the proposed Adaptive Neuro Chromatic Polynomial Fuzzy (ANCPF) rule set. The main type was an ANCPF diagram with a series of record vertices and a series of soft edges, and the next type was an ANCPF diagram with a series of ANCPFs and a series of ANCPF edges. Based on this, ANCPF color polynomials are examined for some ANCPF diagrams. Some interesting comments have been made on the soft chromatic polynomial of the ANCPF diagrams. In addition, some results identified with the idea will be demonstrated. The severity of an OITRD is the amount of its capacity estimated at all vertices, and the full Roman control number marked free on the outside (OITRD number) is the minimum weight of an OITRD. Additionally, a result is recorded.